Effects of Compton scattering on radiometric maps from Rio Preto area, Goiás State, Brazil - Barbosa, Eder Queiroz [UNESP]; Bonotto, Daniel Marcos [UNESP]; Duarte, Cynthia Romariz; Mancini, Luis Henrique (Elsevier, 2025)
Gamma ray spectrometry measurements offer broad utility as a powerful method for identifying and quantifying radionuclides without the need of physicochemical sample preparation. Additionally, in situ readings are non-destructive, preserving the samples integrity. This study aimed to enhance the calibration steps of widely utilized gamma spectrometers based on NaI(Tl) scintillation detectors, involving calculation of combined uncertainties and assessment of systematic effects arising from the interaction of gamma radiation with matter, emphasizing the Compton interference in the gamma spectra. Radiometric data in 272 rock samples from Rio Preto Project developed at Goiás State, Brazil, spanning from 1995 to 2001, were obtained by means of a benchtop gamma spectrometer installed at LABIDRO-Isotopes and Hydrochemistry Laboratory, IGCE-UNESP, Rio Claro (SP), Brazil. The obtained dataset alllowed determine gamma interference factors within the spectral windows of natural radionuclides [K(40K), eU(214Bi), and eTh(208Tl)]. Furthermore, isoline maps were constructed using the geostatistical “minimum curvature” model to data analysis after removal of the Compton interference in spectral windows. Geostatistical models were employed to map their distribution in the study area, contributing to the refinement of procedures adopted for plotting survey/monitoring maps devoted to exploration/environmental purposes, thus, improving the accuracy and comprehension of gamma spectrometric data.
Keywords: Brazilian State of Goiás; Compton scattering; Gamma ray analysis; NaI(Tl) detector; Rio preto project; Uranium exploration